Evaluation of fungicides and bacterial antagonists for management of Corynespora leaf spot on mungbean (Vigna radiata L. Wilczek). (25th February 2022) - Bairwa, Narendra K.; Jambhulkar, Prashant P.; Sushmitha, V.; Arya, Meenakshi; Manjunatha, N.; Bajpai, Ruchira; Singh, Dinesh; Mani, Chandra; Kumar, Shailendra; Chaturvedi, Sushil. K.; Lakshman, Dilip
Abstract: To minimize losses likely to occur due to Corynespora leaf spot, systemic and contact fungicides and formulation of bacterial antagonists like Bacillus subtilis DTBS-5, B. amyloliquefaciens DSBA-11, and Pseudomonas fluorescens DTPF-3 talc-based formulations were evaluated to manage the disease. Though mancozeb has the lowest EC50 value of 1250.54 ppm it was not efficient in the field experiment. In addition, dual culture assay to determine the efficacy of bacterial antagonists against C. cassiicola, B. amyloliquefaciens DSBA-11 effectiovely reduced growth of C. cassiicola. In the field experiments conducted during Kharif 2019 and 2020, two sprays with Azoxystrobin 23 SC@ 0.5 ml lit −1 were found most effective in reducing disease severity by 57.7% and 67.7% respectively during Kharif 2019 and 2020. Azoxystrobin 23 SC treatment resulted in a maximum increase of 281.5 kg in grain yield followed by Pseudomonas fluorescens DTPF-3 264.7 kg and Bacillus subtilis DTBS-5 248.9 kg yield.